Controlling Acung Merchants in the Banjar Customary Tourism Environment - I Nyoman Gede Sugiartha; I Made Minggu Widyantara; I G.A.A.Gita P.Dinar (Community Service Journal of Law, 2022)
As a higher education institution, Warmadewa University must ensure that it always obeys the Tridharma of Higher Education in accordance with the predetermined vision and mission. Now every lecturer is encouraged to be able to package community service activities both in groups and individually which will later show concern for the community. Community service activities can be carried out by providing enlightenment by providing legal counseling and consultation to the community in various fields of life in the field of environment and tourism. One thing that should be observed is environmental conservation in Banjar Pemamoran Kuta, where it is hoped that every Banjar Adat Neighborhood must have a plan for improving environmental management. Environmental conservation which is the values ​​of Balinese society, of course, in its application cannot be ignored even on the pretext of business interests. For the sake of preserving the environment, community members and traditional soldiers need to better understand the efforts that should be pursued and do not hesitate to control the itinerant drink traders who roam the streets of Kuta beach which is also the area of ​​the Pemamoran traditional banjar who trades around every day so that it seems not orderly and does not preserve the tourism environment. In the end, this program is expected to be able to provide understanding and solutions to the community and the Pemamoran Indigenous banjar prajuru to be able to carry out legal control of mobile drink vendors who do not heed the sustainability of the tourism environment in the Pemamoran Indigenous banjar, Kuta Indigenous village, Badung Regency.